X (Twitter) como medio creativo para la producción de microrrelatos en estudiantes de décimo grado de EGB del Colegio de Bachillerato “27 de febrero” - Aguirre Aguilar, Mayra Alejandra (2025)
Nowadays, we live in a globalization era and in the development of the information and communication technologies, therefore the educational institutions, that lead the educational quality, must keep at the vanguard to improve the academic training. This research evaluates the appropriateness of the use of X (twitter) to produce the micro stories in tenth grade students of Basic General Education. Accordingly, it was applied a didactic sequence based on the production of the micro stories. Through the analysis of the produced texts, aspects such as structure, elements and characteristics up to properties of X (Twitter), like length, language and hashtags, were examined. The obtained results show a positive impact on the development of the skills and knowledge, an authentic increase in the production of micro stories, a correct use the established parameters, as well as the properties of X (Twitter). By the semi-structured interviews, a favorable result was confirmed in the use of X for the production of micro stories, an application that was favorable for the communication, collaboration and creativity. In conclusion, it was proved that the use of X (twitter) as a mean of production in the classroom, assists the teaching-learning process and offers alternatives to involve students with new technologies